1989
DOI: 10.1128/aac.33.9.1540
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental salmonellosis in mice with ampicillin-bound nanoparticles

Abstract: We tested the effectiveness of ampicillin bound to nanoparticles of polyisohexylcyanoacrylate (PIHCA) in treating C57BL/6 mice experimentally infected with Salmonella typhimurium C5. The diameter of the nanoparticles was 187 13 nm, and the ampicillin/PIJICA ratio was 0.2/1. The proportion of ampicillin bound was 90 3%. All control mice and all those treated with nonloaded nanoparticles died within 10 days of infection. By contrast, all mice treated with a single i 'ection of 0.8 mg of nanoparticle-bound ampici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(64 citation statements)
references
References 24 publications
2
60
1
1
Order By: Relevance
“…We recently showed with experimentally infected C57BL/6 mice that when ampicillin was linked to nanoparticles of polyisohexylcyanoacrylate (PIHCA), it was more effective in treating acute salmonellosis than free ampicillin (3). We also showed with athymic nude mice that this linkage enhanced the effectiveness of ampicillin in treating chronic listeriosis (9), although Bakker-Woudenberg et al, who used liposome-entrapped ampicillin, observed no such enhancement (2).…”
mentioning
confidence: 77%
“…We recently showed with experimentally infected C57BL/6 mice that when ampicillin was linked to nanoparticles of polyisohexylcyanoacrylate (PIHCA), it was more effective in treating acute salmonellosis than free ampicillin (3). We also showed with athymic nude mice that this linkage enhanced the effectiveness of ampicillin in treating chronic listeriosis (9), although Bakker-Woudenberg et al, who used liposome-entrapped ampicillin, observed no such enhancement (2).…”
mentioning
confidence: 77%
“…[31][32][33] Previous studies throughout the literature have applied lipid-based approaches (liposomes, solid lipid nanoparticles, nanoemulsions, and microemulsions) and polymerbased nanocarriers (nanocapsules and nanospheres) to enhance the antimicrobial activity of antibiotics (including β-lactams). [34][35][36][37][38][39] Nanoantimicrobial agent synthesis studies have recently increased in number; however, most of these agents are nonantibiotic-based nanoparticles, primarily metal-based nanoparticles that use silver, copper, and zinc, among other metals. This study aimed to prepare the first amp-chitosan-iron oxide nanocomposite for numerous applications such as a novel nanoantibiotic pharmaceutical agent to combat various bacterial diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Higher intracellular concentrations of antibiotics enhance the antibacterial activity of phagocytic cells against to intracellular infections when compared to the same free drug dose (Emmen and Storm, 1987;Bas et al, 2000). It was reported that LA and ampicillin- Bakker-Woudenberg et al, 1986;Carryn et al, 2003) or experimental salmonellosis (Fattal et al, 1989), listeriosis (Bakker-Woudenberg et al, 1985, 1988Fattal et al, 1991). On the contrary, it was reported that FA had no good bactericidal activity, nor need higher concentrations to the treatment in the intracellular infections caused by non-typeable Haemophilus influenzae (Ahren et al, 2002), non-typhoid Salmonella (Chiu et al, 1999) or experimental salmonellosis (Fattal et al, 1989).…”
Section: Resultsmentioning
confidence: 99%